Inducible RNA Interference of brlAβ in Aspergillus nidulans - Barton, L. M. (American Society for Microbiology (ASM), 2008)
An inducible RNA interference (RNAi) construct composed of inverted repeating alcA promoters flanking the developmental regulatory gene brlAβ was tested in Aspergillus nidulans. On inducing medium, the RNAi strains failed to sporulate and lacked brlAα and brlAβ expression. RNAi was specific for brlAβ, but not brlAα, silencing, indicating brlAα regulation by brlAβ.